The role of some psychological factors in the doping attitudes of elite wrestlers - Sheikh Ismaili, S.; Yousefi, B.; Sobhani, Y. (International Journal of Wrestling Science, 2013)
The fight against doping is a challenging task. Doping is a complicated phenomenon, thus the purpose of this study was to investigate relationships between doping attitudes and other psychological factors. Methods: Fifty-five competitive elite male wrestlers (Age: 25.63 ± 3.14 yrs; Height: 173.46 ± 4.27cm) from the Kermanshah and Kurdistan states of Iran were participants in this study. All subjects completed the Performance Enhancement Attitude Scale (PEAS), Sport Multidimensional Perfectionism Scale (MPS), Form V of the Sensation Seeking Scale, Task and Ego Orientation in Sport, Trait Sport Confidence Inventory and the Doping Use Belief questionnaires. Results: Pearson's correlation coefficients showed a significant positive correlation between the PEAS with Doping belief (r=.582, p<.01), Disinhibition (r=.388, p<.01), Perceived Coach Pressure (r=.329, p<.05) and Concern over Mistakes (r=.298, p<.05) and had significant negative correlation with Task orientation in Sport (r=-.363, p<.01). Multiple regression showed the combination of psychological factors significantly contributing to the prediction of Doping Attitude; F (4, 43) = 6.84, p < .001, R2= .33. Conclusion: It is obvious that the most effective approach in the fight against doping is prevention, thus the identification of athletes who score high in the personal characteristics of perfectionism, sensation seeking and goal orientation in sport could be helpful information for coaches and team physicians, in order to detect, monitor and further work with the athletes that may be at higher risk for doping.